PH‐Responsive Aminomethyl Functionalized Poly(p‐xylylene) Coatings by Chemical Vapor Deposition Polymerization. Issue 9 (21st February 2017) - Koenig, Meike; Kumar, Ramya; Hussal, Christoph; Trouillet, Vanessa; Barner, Leonie; Lahann, Joerg
Abstract : The preparation of a pH‐responsive poly( p ‐xylylene) derivative via chemical vapor deposition polymerization can be achieved by modification of the paracyclophane precursor with ionizable aminomethyl groups. The swelling behavior is investigated using spectroscopic ellipsometry and streaming potential measurements. The capacity regarding the coating of complex substrates with stimuli‐responsive films is demonstrated by coating filter paper. Abstract : The preparation of stimuli‐responsive aminomethyl functionalized poly( p ‐xylylene) coatings by chemical vapor deposition polymerization is reported. Modification of the paracyclophane precursor with ionizable aminomethyl groups leads to polymer coatings with pH‐responsive swelling properties. The swelling behavior is monitored in situ using spectroscopic ellipsometry and additional streaming potential measurements are performed. With decreasing pH‐value, the coating becomes increasingly charged and reversibly swells to several times its dry thickness. The swelling ratio is sensitive to the ionic strength of the solution. By using a mixture of unfunctionalized and functionalized precursors in the chemical vapor deposition process, the number of charges in the polymer layer can be tuned and with it the swelling ratio of the coating. As a proof‐of‐concept for possible applications, a commercial paper filter is coated. This results in a pH‐dependent wetting behavior and pH‐dependent transport through the capillaries of the paper.